(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study was conducted on 30 patients and 20 healthy people to determine the influences of infected with Treponema pallidum on levels of IgM , IgA, IgG ,Complement4 ,complement 3 and some Blood parameters in infected with T. Pallidum also relation disease with blood factions in compared with healthy group who have visited Al-Sadder Medical City and Al-Hakeem Hospital in Al- Najaf governorate during the period from August 2014 till February 2015 in Al-Sadder Medical City Laboratories .The results showed significant increase (P<0.001) in IgM , IgG ,Complement4 in T. pallidum infected patients in compared to control group. Furthermore the results showed C3 was significant decreased (P< 0.05) in Treponema Pallidum infected patients in compared to control group also the results showed significant increase in WBCs, RBCs ,MPV and HCT level and significant decrease in MCV in patients compared with control group . The study also showed that the people of blood type A are more prone to infection, followed by blood type B and O, while there are no injuries to the blood type AB.